Cartels disrupt a country's food security - Abdul Samad, Abdul Rahim (Pusat Strategi Dan Perhubungan Korporat, Universiti Putra Malaysia, 2024)
Cartels pose a significant threat to fair competition and food security in Malaysia. These illicit groups manipulate markets, often through price fixing agreements, stifling innovation and harming consumers through artificially high prices. This not only hurts ordinary Malaysians but also disadvantages honest businesses struggling to compete.